Enhancement of Solubility of Albendazole by Inclusion Complexation with Nanosponges and β-Cyclodextrin - Rao, Monica Raghavendra Prasad; Sakharwade, Saloni A. (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim: Objective of work was to compare role of β-Cyclodextrin (β-CD) and Nanosponges (NS) prepared with different cross-linking ratios and different drug loading ratios to enhance solubility and dissolution rate of Albendazole (ALB). Materials and Methods: Diphenyl Carbonate (DPC) was used as cross-linker for preparing NS with various β-CD and DPC ratios (1:2 and 1:4). Solvent evaporation was used to make binary complex. ALB and NS were dissolved in Dichloromethane (DCM) in 1:1 and 1:2 ratios and triturated until solvent evaporated. Phase solubility, saturation solubility and in vitro dissolution studies were performed. Solid state characterization as well as spectral and thermal analyses was done. Results: Stability constant for complexes ALB-β-CD, ALB-NS (1:2 ratios) and ALB-NS (1:4 ratios) were found to be 1715M-1±18.3, 1902M-1±29.5 and 1945M-1±30.1 respectively. Maximum solubility of all complexes was observed in fed state simulated intestinal fluid (FeSSIF). The increase was to the tune of 3-8 folds for all binary complexes at 1:1 and 1: 2 drug loading ratios. Dissolution rate increased by 47%-67% for drug loading ratio 1:1 and 55-71% for drug loading ratio 1:2 in FeSSIF in 150 min. Conclusion: β-CD based NS improved solubility of ALB. Presence of drug in molecular form in nanochannels and amorphization were responsible for increase in solubility. Nanosponges prepared in ratio 1:4 and drug loading in ratio 1:2 showed highest increase in solubility and dissolution rate.
Keywords: β-cyclodextrin; Binary complex; Nanosponges; Albendazole